Principal leadership at vocational high school: Center of excellence (SMK PK) Muhammadiyah 2 Pekanbaru - Wardani, Tri Febri; Raihani, Raihani (Asatiza: Jurnal Pendidikan, 2024)
The "Center of Excellence" (SMK PK) is a program launched by the Ministry of Education and Culture to enhance the quality and performance of vocational schools through partnerships with business and industry. This study explores the leadership of the principal at SMK PK Muhammadiyah 2 Pekanbaru within the context of the program. Using a qualitative approach, data were gathered through interviews, documentation, and observation from the principal, head of administration, and vice principal of curriculum. The findings reveal six key leadership indicators: creating an effective school, professional development of staff, improving student achievement, fostering entrepreneurship, driving innovation, and establishing collaborations. Factors influencing leadership were categorized into supporting (e.g., communication, participatory leadership) and inhibiting (e.g., stakeholder disagreement, teacher reluctance).